2020
DOI: 10.3390/molecules25112502
|View full text |Cite
|
Sign up to set email alerts
|

Propionic Acid and Fasudil as Treatment against Rotenone Toxicity in an In Vitro Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a multifactorial neurodegenerative disease. In recent years, several studies demonstrated that the gastroenteric system and intestinal microbiome influence central nervous system function. The pathological mechanisms triggered thereby change neuronal function in neurodegenerative diseases including dopaminergic neurons in Parkinson´s disease. In this study, we employed a model system for PD of cultured primary mesencephalic cells and used the pesticide rotenone to model dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…In addition to neurite length, neurite arborization quantified by our assay also was reduced depending on applied Rotenone concentrations. Concentrations used in this work were in line with other studies that have employed a Rotenone model on similarly differentiated SH-SY5Y cells [50,51] and on MDN [15,52].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition to neurite length, neurite arborization quantified by our assay also was reduced depending on applied Rotenone concentrations. Concentrations used in this work were in line with other studies that have employed a Rotenone model on similarly differentiated SH-SY5Y cells [50,51] and on MDN [15,52].…”
Section: Discussionsupporting
confidence: 80%
“…Due to the multifactorial character of PD an effective treatment strategy would have to target several pathological processes at a time. Therefore, approaches to prevent neuronal death [ 13 , 14 , 15 ], to replace neuronal cells [ 16 ] or to modulate inflammation and targeting aSYN have been followed [ 3 , 15 ]. While still no disease modifying approaches have shown to be effective, details of PD pathogenesis and of putative new therapeutic avenues are intensely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although propionic acid might act on FFAR3 in the gut and ameliorate motor deficits and dopaminergic neuron loss in 6-hydroxydopamineinduced PD mice [14], it is possible that the circulating propionic acid directly protects neurons in the brain. An in vitro experiment showed that treatment with propionic acid prevented dopaminergic neurons from the neurotoxicity of rotenone and enhanced the outgrowth of neurites [26]. Moreover, as an HDAC inhibitor [11], propionic acid might also inhibit the neuroinflammatory activation and attenuate the damage of blood-brain-barrier [27], the two characteristic pathological changes in PD brain [28].…”
Section: Discussionmentioning
confidence: 99%
“…196 A recent study on the effect of propionate on rotenone-treated dopaminergic neurons showed that the survival rate of TH+ dopaminergic neurons increased significantly, indicating that propionic acid increased the expression of the TH gene, decreased the expression of the α-syn gene, and increased the expression of intracellular STAT3 protein to promote neuroprotection. 197 In addition, SCFAs from intestinal microbiota are a key molecule regulating the maturation, morphology and function of microglia. 147 Microglial defects in GF mice are reversible and can be reconstructed by reintroducing microbial metabolites such as SCFAs.…”
Section: Short Chain Fatty Acids (Scfas)mentioning
confidence: 99%